Optimizing the role of Baitul Maal Darussalam in Gandusari Village, Bandongan District to increase public awareness in the utilization of zakat through video media - Fahmi Medias; Ari Wibiyono; Bagus Aprianto; Sanjaya Hadi Saputra; Rabudi Rabudi; Rahmanudin Rahmanudin (Universitas Muhammadiyah Magelang, 2022)
Baitul Mal Darussalam as one of the institutions under the auspices of LazisMu Bandongan has a role in increasing public awareness in the utilization of zakat. The problem faced by LazisMu is increasing the contribution and awareness of the wider community, so that they are willing to pay zakat mal. LazisMu Bandongan created a program called